2011
DOI: 10.1007/s12306-011-0158-z
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive repair of acute Achilles tendon ruptures with Achillon device

Abstract: The subcutaneous rupture of the Achilles tendon is a frequently observed lesion. Its treatment, however, remains controversial. The treatment to be applied varies between the conservative method, open surgical procedure and percutaneous or minimally invasive techniques. While conservative treatment results in a high percentage of re-ruptures, the open surgical treatment also has its complications. Surgical wound dehiscence, delayed cutaneous healing due to infection, delayed weight-bearing capacity, and conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…In 2012, Diao et al [71] reported favorable short-term clinical outcomes using the Achillon device (Integra, Plainsboro, NJ). Similar favorable findings were demonstrated in numerous other studies [72][73][74][75] with regard to functional outcome, better cosmetic appearance, less wound complications, patient satisfaction, and imaging results using percutaneous techniques (Fig. 2).…”
Section: Percutaneous Techniquessupporting
confidence: 89%
“…In 2012, Diao et al [71] reported favorable short-term clinical outcomes using the Achillon device (Integra, Plainsboro, NJ). Similar favorable findings were demonstrated in numerous other studies [72][73][74][75] with regard to functional outcome, better cosmetic appearance, less wound complications, patient satisfaction, and imaging results using percutaneous techniques (Fig. 2).…”
Section: Percutaneous Techniquessupporting
confidence: 89%
“…There were no re-ruptures at 1 year and most resumed sporting activities at 6 months. Other authors have been able to reproduce similar results with the Achillon technique whilst reporting none of the surgical complications above [77].…”
Section: Percutaneous Repairsupporting
confidence: 53%
“…Recently, percutaneous repair techniques have been adopted as new operative procedures that attempt to reduce complications caused by open surgery and has exhibited good efficacy. An up-to-date systematic review performed by Khan et al [25], along with several most recent studies [37][38][39][40][41][42], indicate that compared with open repair, percutaneous repair results in a lower complication rate. Moreover, Maffulli et al [43,44] proved that percutaneous repair of Achilles tendon was not only available for diabetic patients but also suitable for patients >65 years.…”
Section: Discussionmentioning
confidence: 99%